Boomer marketing [electronic resource] : selling to a recession resistant market - Chaston, Ian (Routledge, 2009)
Baby boomers (consumers in the 50+ age bracket) are the wealthiest, fastest growing consumer group in the world. In this book, the author uses original case material to propose strategic solutions that take advantage of the moneyed segments of the maturing boomer market. It is useful for students of marketing and consumer behaviour.